New York City / Eleanor Berman - Berman, Eleanor
Experience the best of New York City with DK Eyewitness Travel Guide: New York City. This newly updated travel guide for New York City will lead you straight to the best attractions Manhattan has to offer, from unearthing archaeological treasures at The Metropolitan Museum of Art to biking through Central Park to discovering the city's hottest neighborhoods on walking tours. Plus, check out the best of the boroughs with suggested highlights for Brooklyn, Queens, Staten Island, The Bronx, and upper Manhattan.